Corneal Haze after Wavefront Guided PRK at Dr Yap Eye Hospital Yogyakarta: Is There Any Difference Between Low And High Myopia? - Dede Neni Herani; Suhardjo Suhardjo (Majalah Oftalmologi Indonesia, 2015)
Background: Wavefront guided Photorefractive Keratectomy (PRK) has regained its popularity. However corneal haze after this procedure often follows. Five to 15% of PRK patients developed corneal haze. The purpose to investigate whether the presence of corneal haze after PRK in low, moderate, and high myopia patients are different and whether these differences influence visual outcomeMethod: This was a restrospective cohort study of 589 eyes underwent PRK at Yap Eye Hospital between 2011 and 2012. Visual acuity, refractive status, and corneal haze were examined at 6 times follow up after PRK. Corneal haze was defined as persistent hazy found at three times follow up including the fifth and sixth follow up.Result: There were 207 males and 77 females with mean age 23,2 years who has clear cornea and 21.5 whose hazy cornea. We found 11.5% of corneal haze in low myopia and 11.2% in high myopia. The proportion of corneal haze in different severity of myopia was not statistically significant (p=0.38). Regardless of the presence of corneal haze, the final visual outcome afterPRK wavefront guided was overall good to excellent (1.00). However the corneal haze condition was resolved ini six months after.Conclusion: The presence of corneal haze after wavefront guided PRK was similar across different severity of myopia. The presence of corneal hazedid not influence the final visual outcome, which was overall good to excellent.Â Keywords: wavefront guided PRK, myopia, corneal haze, visual outcome